Clinical effectiveness and acceptability of structured group psychoeducation versus optimised unstructured peer support for patients with remitted bipolar disorder (PARADES): a pragmatic, multicentre, observer-blind, randomised controlled superiority trial - Morriss, Richard; Lobban, Fiona; Riste, Lisa; Davies, Linda; Holland, Fiona; Long, Rita; Lykomitrou, Georgia; Peters, Sarah; Roberts, Christopher; Robinson, Heather; Jones, Steven (Elsevier, 2016)
Background